Secured protection of transmission line by distance relay using data mining approach - M. Kiruthika; Bindu S. (Institute of Advanced Engineering and Science, 2021)
Distance relay is one of the most important protection element of a transmission line used in protection schemes. Relay may malfunction if it is not able to distinguish faults from system stressed conditions. This work mainly focusses on enhancing the performance of the distance relay in a secured manner based on data mining approach which uses two phases of classification. Level 1 classifier identifies the system conditions like normal, fault, and power swing and level 2 classifier gets initiated when there is a power swing and distinguishes between the persistence of power swing condition and a three-phase fault. In both the phases, the protection scheme in the respective zone where the fault occurred gets activated. The proposed methodology is tested for an IEEE 9-bus system wherein the data is collected from phasor measurement units placed in optimal locations. Optimal PMU placement is economical since it overcomes issues like cost, communication infrastructure issues, maintenance and complexity. The results proved that the proposed method is effective with good efficiency and higher accuracy with less number of PMUs.